2000
DOI: 10.1136/bjo.84.9.963
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow up of premature infants: detection of strabismus, amblyopia, and refractive errors

Abstract: Aim-To establish recommendations for long term ophthalmological follow up of prematurely born infants. Methods-130 infants with a gestational age (GA) <37 weeks and born between 1 November 1989 and 31 October 1990 were enrolled in a prospective study about the development of strabismus, amblyopia, and refractive errors. Infants were subdivided in three groups according to GA: A <28 weeks (n=32), B >28-<32 weeks (n=64), C >32-<37 weeks (n=34). Ophthalmological assessment took place at the postconceptional age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
3
9

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 12 publications
1
54
3
9
Order By: Relevance
“…on average more mature neonates than in the present cohort (Darlow et al 1997;Holmstro¨m et al 2006), and for published data on ELBW children (14%) (Hebbandi et al 1997). Other researchers have found that the rate of strabismus increases with decreasing GA (Schalij-Delfos et al 2000), and in a population-based cohort of children with GA <26 weeks, 24% had strabismus (Marlow et al 2005). Such an association was not obvious in our study, but the cohort was too small to draw a firm conclusion.…”
Section: Discussioncontrasting
confidence: 47%
“…on average more mature neonates than in the present cohort (Darlow et al 1997;Holmstro¨m et al 2006), and for published data on ELBW children (14%) (Hebbandi et al 1997). Other researchers have found that the rate of strabismus increases with decreasing GA (Schalij-Delfos et al 2000), and in a population-based cohort of children with GA <26 weeks, 24% had strabismus (Marlow et al 2005). Such an association was not obvious in our study, but the cohort was too small to draw a firm conclusion.…”
Section: Discussioncontrasting
confidence: 47%
“…Although it is commonly reported that preterm children have poorer visual outcomes in specific measures and higher rates of impairment compared with term controls, previous studies have typically reported on selected samples with a focus on participants with severe white matter lesions and/or a previous diagnosis of ROP. 2,[16][17][18][19][20] In a cohort study by Evensen et al 41 of 14-year-olds free of cerebral palsy who were born ,1500 g in the 1980s, rates of impaired visual acuity (8%) and stereopsis (8%) were lower, but rates of convergence problems (24%) were higher than the current study.…”
Section: Visual Perceptioncontrasting
confidence: 44%
“…1,42 To develop normal stereopsis the neural development of binocular cortical cells requires clear retinal imaging during critical periods of visual development, which, according to Banks et al (1975), 43 is between 3 and 6 months, and between 12 and 20 months. Refractive errors, strabismus, and amblyopia are often reported in preterm children 9,20,44,45 whose eyes may be susceptible to damage owing to necessary medical care and/or early visual experiences during critical periods of development, which may help explain why there is a higher incidence of reduced depth perception, even in adolescence. Convergence and reduced or absent stereopsis have important implications for functional vision, such as activities requiring motion perception, 46 and many visual motor activities including reaching, manipulation of objects, and the ability to guide one' s body or a vehicle in the environment.…”
Section: Visual Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,[43][44][45][46][47] This variation has implications on the planning of long-term surveillance and care for low birth weight infants, in terms of when to assess the child. It would be beneficial if risk factors for the development of strabismus were identified, to minimise assessments required for maximum capture.…”
Section: Strabismusmentioning
confidence: 99%